Brief account of the development of speleology in Slovenia (to 1914) - Kranjc, Andrej (Acta carsologica, 1997)
The most important predecessors in speleology are Valvasor, Nagel and Hacquet, and the explorers of the first shaw caves (Vilenica, Postojnska jama, Škocjanske jame). In the first half of the 19th century the most important speleological explorations were those intended to find drinking water sources for Triest, and in the second half the explorations of deep potholes and big water caves of Notranjsko. In the years 1882 ("Slovenski gadje") and 1883 the period of organised caving activity began.
Keywords: kraške jame; List of caves in Slovenia; Slovenia; Slovenija; speleologija; zgodovinski pregledi